ANALISIS PEMASARAN JAGUNG DI DESA DIMEMBE KECAMATAN DIMEMBE KABUPATEN MINAHASA UTARA - Cendy Claudia Wowiling; Lyndon R. J. Pangemanan; Joachim N. K. Dumais (AGRI-SOSIOEKONOMI, 2018)
The purpose of this research is to analyze the marketing of corn in each marketing channel in the village of Dimembe, Dimembe Subdistrict, North Minahasa Regency. The data used in this study are primary and secondary data. Primary data was obtained from interviews with 15 farmers while secondary data from the Village Office, North Minahasa Statistics Agency and the North Sulawesi Provincial Statistics Agency. The sampling method used the snowball sampling method. Data analysis methods are analysis of Marketing Channel, Marketing Agency, Marketing Margin and Marketing Costs. The results showed that there were three types of marketing channels, namely the first marketing channel: Farmers to Consumers; second marketing channel 2 from Farmers toRetailers then to Consumers; and the third marketing channel from Farmers to Collector Traders then arrived at the Consumer. Marketing margin on marketing channel I is Rp 213.33 / kg, on marketing channel II is Rp 1,500.00 / kg, and on marketing channel III is Rp 2,500.00 / kg. The highest share received by farmers is in the marketing channel I at 93.90%. While the lowest share received by farmers is in marketing channel III, which is equal to 58.33%. Thus it can be concluded that the longer the marketing channel, the greater the marketing margin and vice versa. And also the shorter the marketing channel the greater the share received by the farmer and vice versa. *lrr + eprm *